Stimulation of hyaluronan biosynthesis by platelet-derived growth factor-BB and transforming growth factor-beta 1 involves activation of protein kinase C. - Suzuki, M (1995)
The intracellular signal transduction pathways that mediate the stimulatory effects of platelet-derived growth factor (PDGF)-BB and transforming growth factor (TGF)-beta on hyaluronan biosynthesis in human fibroblasts were investigated. The stimulatory effects of both PDGF-BB and TGF-beta 1 were dependent on protein kinase C (PKC), since the PKC inhibitor calphostin C inhibited the stimulation by the growth factors. Direct activation of PKC by phorbol 12-myristate 13-acetate (PMA) also stimulated hyaluronan production, and the combination of either PDGF-BB or TGF-beta 1 and PMA gave an increased effect. One possible mechanism for activation of PKC is via induction of phospholipase C (PLC) activity; U-17322, an inhibitor of PLC-gamma, was found to inhibit partially PDGF-BB-stimulated hyaluronan synthesis. PDGF-BB is known to activate PLC-gamma through tyrosine phosphorylation; however, a PDGF beta-receptor mutant unable to interact with and activate PLC-gamma was still able to mediate induction of hyaluronan biosynthesis, indicating that PDGF-mediated stimulation is not entirely dependent on PLC-gamma. The stimulations by PDGF-BB and TGF-beta 1 were partly dependent on protein synthesis, since parts of the effects were inhibited by cycloheximide; in contrast, the effects mediated by PMA were not. Our results indicate that PKC is involved in the transduction of the effects of growth factors on hyaluronan biosynthesis, and that the effects involve direct or indirect activation of existing hyaluronan synthetase molecules, as well as induction of new enzyme molecules.